2010
DOI: 10.1002/hed.21303
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative predictors of sternotomy need in mediastinal goiter management

Abstract: Background. The objective of this study was to identify the preoperative risk factors for patients in need of a sternotomy in the management of mediastinal goiters in order to provide better preoperative planning and patient consent.Methods. We analyzed 98 patients who underwent surgery for mediastinal goiters (goiters extending below the thoracic inlet 3 cm with the neck in hyperextension) between 1995 and 2008. Twelve (12.2%) of the patients required a sternotomy. The patients' features were analyzed by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 19 publications
(18 reference statements)
2
46
0
3
Order By: Relevance
“…There is no consensus when a thoracic approach is required. Several studies suggested that reoperative surgery for a mediastinal thyroid mass, posterior location, and subcarinal extension increase the risk for a sternotomy [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…There is no consensus when a thoracic approach is required. Several studies suggested that reoperative surgery for a mediastinal thyroid mass, posterior location, and subcarinal extension increase the risk for a sternotomy [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…While most of these retrosternal goitres can be excised through a standard cervical collar incision, 4-12% of patients will require an additional thoracic incision such as a manubriotomy, sternotomy, thoracotomy or mediastinotomy. [1][2][3][4][5] Although these incisions facilitate the removal of the goitre, they are invasive and involve disruption of the thoracic skeleton. They may therefore result in significant morbidity including pain, prolonged hospital stay and recovery.…”
mentioning
confidence: 99%
“…The majority of patients, in addition to neck swelling may present with shortness of breath or stridor. Other symptoms include hoarseness, dysphagia, and about 50% of patients may be asymptomatic [16]. Thyrotoxicosis symptoms were reported in less than 10% of case [17].…”
Section: Discussionmentioning
confidence: 99%